Genome-wide mapping of global-to-local genetic effects on human facial shape - Claes, Peter; Roosenboom, Jasmien; White, Julie D.; Swigut, Tomek; Sero, Dzemila; Li, Jiarui; Lee, Myoung Keun; Zaidi, Arslan; Mattern, Brooke C.; Liebowitz, Corey; Pearson, Laurel; González, Tomás; et al. (Nature genetics, 2018)
Genome-wide association scans of complex multipartite traits like the human face typically use preselected phenotypic measures. Here we report a data-driven approach to phenotyping facial shape at multiple levels of organization, allowing for an open-ended description of facial variation while preserving statistical power. In a sample of 2,329 persons of European ancestry, we identified 38 loci, 15 of which replicated in an independent European sample ( n = 1,719). Four loci were completely new. For the others, additional support ( n = 9) or pleiotropic effects ( n = 2) were found in the literature, but the results reported here were further refined. All 15 replicated loci highlighted distinctive patterns of global-to-local genetic effects on facial shape and showed enrichment for active chromatin elements in human cranial neural crest cells, suggesting an early developmental origin of the facial variation captured. These results have implications for studies of facial genetics and other complex morphological traits. The authors report a data-driven approach to phenotyping 3D facial shape. They apply their methodology to 2,329 individuals of European ancestry and identify 38 loci that associate with specific facial morphologies, some of which overlap with neural-crest-specific regulatory regions.